Evaluation of Microleakage and Biocompatibility of Universal Adhesive Containing Titanium Dioxide Nanoparticles: A Comparative In Vitro Study - Fatemeh koohpeima; Mohammad Javad Mokhtari; Marzieh Salari (Fasa University of Medical Sciences, 2021)
Background & Objective: Although dental composites have undergone a high level of development in recent years, there are still difficulties including microleakage. The incorporation of nanoparticles (NPs) in dental materials can produce antibacterial effects, but the effect of TiO2 NPs on microleakage has not yet been investigated. The present study aimed to determine the effect of TiO2 NPs incorporation in the universal single bond and pretreatment with them on microleakage of clV cavities using both total-etch and self-etch approaches. Materials & Methods: Standard clV cavities were prepared on the buccal surfaces of the sixty non-carious human molar teeth. The restoration of samples was carried out with 6 different methods and randomly divided into six groups of ten subjects. Microleakage in both gingival and occlusal margins was determined after placement in 2% basic fuschin solution for 24h. Biocompatibility of a universal single bond was evaluated by MTT assay. Results: In both occlusal and gingival margins in all groups, the application of TiO2 NPs was better than no application. We observed the relatively low cytotoxic effect of TiO2 NPs incorporated in the universal adhesive on NIH-3T3 cell viability. Conclusion: Regarding the limitations of the present investigation, using TiO2 NPs with both total-etch and self-etch approaches to universal single bond may lead to a decrease in the microleakage of resin composite restorations.